An investigation into linguistic features of comparative structures in business english and vietnamese online newspapers (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Business has been developing more and more in our society and it provides customers with products and services. Therefore, business newspapers play a crucial role in providing business information and keeing people updated in a business world. Thus, how to write a business articles effectively should be paid considerable attention. The study aims at analyzing the linguistic features of comparative structures in business English and Vietnamese online newspapers as well as discovering similarities and differences between the two languages in terms of syntactic, semantic and cohesive features. The findings show that comparative structures in business English and Vietnamese online newspapers employ a variety of syntactic features such as: nominal comparatives, adjectival comparatives and adverbial comparatives. In addition, there is a particular use of comparative structures that is particular to business newspapers: comparative structures describing trends, promoting products and expressing speculations. Besides, reference, ellipsis, conjunction and repetition are also exploited in comparative structures in business English and Vietnamese online newspapers. The research result is hoped to be of some contribution to the writers, especially journalists and help them be more aware of the importance of comparative structures in writing an effective business newspapers in a business world.